Nogo-A-deficient Transgenic Rats Show Deficits in Higher Cognitive Functions, Decreased Anxiety, and Altered Circadian Activity Patterns - Petrasek, Tomas; Prokopova, Iva; Sladek, Martin; Weissova, Kamila; Vojtechova, Iveta; Bahnik, Stepan; Zemanova, Anna; Schönig, Kai; Berger, Stefan; Tews, Björn; Bartsch, Dusan; Schwab, Martin; et al. (Frontiers in Behavioral Neuroscience, 2014)
Decreased levels of Nogo-A dependent signaling have been shown to affect behavior and cognitive functions. In Nogo-A knockout and knock-down laboratory rodents, behavioral alterations were observed, possibly corresponding with human neuropsychiatric diseases of neurodevelopmental origin, particularly schizophrenia. This study offers further insight into behavioral manifestations of Nogo-A knockdown in laboratory rats, focusing on spatial and non-spatial cognition, anxiety levels, circadian rhythmicity and activity patterns. Demonstrated is an impairment of cognitive functions and behavioral flexibility in a spatial active avoidance task, while non-spatial memory in a step-through avoidance task was spared. No signs of anhedonia, typical for schizophrenic patients, were observed in the animals. Some measures indicated lower anxiety levels in the Nogo-A deficient group. Circadian rhythmicity in locomotor activity was preserved in the Nogo-A-knockout rats and their circadian period (tau) did not differ from controls. However, daily activity patterns were slightly altered in the knockdown animals. We conclude that a reduction of Nogo-A levels induces changes in CNS development, manifested as subtle alterations in cognitive functions, emotionality and activity patterns.